DEUTSCHE WELLE’S COVERAGE OF PALESTINE AND ISRAEL FROM DECEMBER 1st TO DECEMBER 8th 2023: A CRITICAL DISCOURSE ANALYSIS - Nurromadini, Zahirah Soraya; Suganda, Sonya Puspasari (International Review of Humanities Studies, 2024)
The attacks on October 7th, 2023 sparked a new wave of escalation between Israel and Palestine with global news coverage. Though there is coverage on both sides, many are calling out the Western news media for being biased in their reports. This paper explores the diction used by Deutsche Welle (DW) when reporting Palestine and Israel from December 1st to December 8th, 2023. The paper will use the Critical Discourse Analysis (CDA) theory by Norman Fairclough to process the data using a qualitative approach. The study aims to examine whether the diction used by DW journalists in their reports reflects DW’s stance of being impartial. The findings show that although DW tries its best to seem impartial, its reports are still heavily influenced by Germany’s stance in supporting Israel.